Effect of educational and support interventions to increase long-term breastfeeding rates in primiparous women: a systematic review protocol. (March 2017) - Meedya, Shahla; Fernandez, Ritin; Fahy, Kathleen
Abstract : Review question/objective: The objective of this review is to identify the effects of educational and supportive interventions provided by health professionals on long-term breastfeeding rates at six months and up to two years post partum among primiparous women who intend to breastfeed.